2007
DOI: 10.1016/j.alcohol.2007.03.009
|View full text |Cite
|
Sign up to set email alerts
|

A new meaning for “Gin & Tonic”: tonic inhibition as the target for ethanol action in the brain

Abstract: Gamma-aminobutyric acid (GABA) is the main chemical inhibitory neurotransmitter in the brain. In the central nervous system (CNS) it acts on two distinct types of receptor: an ion channel, i.e., an "ionotropic" receptor permeable to Cl -and HCO 3 -(GABA A receptors) and a G-protein coupled "metabotropic" receptor that is linked to various effector mechanisms (GABA B receptors). This review will summarize novel developments in the physiology and pharmacology of GABA A receptors (GABA A Rs), specifically those f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 85 publications
(109 reference statements)
1
56
1
Order By: Relevance
“…Tonic inhibition is mediated predominantly by extrasynaptic ␦ subunit-containing GABARs Mody et al, 2007). A unique finding of this study was that, unlike the surface expression of the ␤2/3 and ␥2 subunits, the surface expression of the ␦ subunit in the SE-treated slices was not reduced after in vivo SE.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Tonic inhibition is mediated predominantly by extrasynaptic ␦ subunit-containing GABARs Mody et al, 2007). A unique finding of this study was that, unlike the surface expression of the ␤2/3 and ␥2 subunits, the surface expression of the ␦ subunit in the SE-treated slices was not reduced after in vivo SE.…”
Section: Discussionmentioning
confidence: 67%
“…In an in vivo study (Naylor et al, 2005), SE resulted in altered GABA-mediated inhibition and a diminished colocalization of the ␤2/3 and ␥2 GABAR subunits with synaptic markers. Although the second study found an increase in tonic inhibition, neither study directly assessed changes in the trafficking of the extrasynaptic ␦ subunit-containing GABARs, the prime mediators of tonic inhibition Mody et al, 2007). These studies also offered two different explanations for the increased trafficking of GABARs during SE.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Conversely, anoxiatolerant turtle cortical neurons likely do not express extrasynaptic GABA A Rs because they lack an observable tonic current. This is not uncommon; many cell types do not express these receptors (32). More importantly, because E GABA is depolarizing relative to V m in normoxic turtle brain, any tonic GABAergic activity would be excitatory, and therefore the absence of such a tone in this model is not surprising.…”
Section: Discussionmentioning
confidence: 99%
“…Tonic currents are mediated by extrasynaptic GABA A Rs and set the excitability threshold for neurons in adult mammalian brain (32). Baseline tonic inhibition is typically >50 pA, and this activity increases greater than twofold postischemic insult in mammals and impairs functional recovery following stroke (9,33).…”
Section: Discussionmentioning
confidence: 99%